Dampak Transformasi Era Digital Terhadap Manajemen SDM khususnya Kepala Sekolah - Eni Veronika; Usman Radian (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
In the world of digital-based education, perspectives regarding human resource management (HR) have also changed. This article discusses how digital transformation affects HR, especially school principals, by focusing on how technology is used in assisting, digital skills development, and paradigm shifts. School principals and teachers now need to focus on their digital skills, in this pre-digital era, administration received a lot of attention. It is important to have digital skills because schools require all school principals and educators as well as all school staff to be able to use information technology in accordance with the needs of the world of education in this digital era. A competency-based approach makes more sense for dealing with technological change. Human resource management is very important for a school to be able to adapt and develop in a rapidly developing digital world